Transnational Routes and Family Life: the letters from a Cape Verde immigrant in Brasil - Mesquita, W.; Cordeiro, Graça Índias (First International Conference on Cape Verdean Studies, 2015)
The Cape Verde diaspora is characterized by a large diversity of routes, flows and destinies, mostly throughout America and Europe. Such migration processes involve a variety of transnational relations and of articulations that never cease to surprise us. Following the trend initiated in the social sciences by Thomas and Znaniecky with their 1918 publication of the letters exchanged between Polish immigrant peasants in the USA and their families, we propose to analyse a collection of 20 letters that are part of the family archive of a Cape-Verdean immigrant in Brasil born in 1901 in the island of São Nicolau and deceased in 1992 in Rio de Janeiro. Through an analysis of these letters, particularly their different forms, contents and use of the language it is possible to identify specific functions, as the need to maintain group attachments and family identification processes. With this paper we propose not only to identify some of the specificities of the Cape Verde migrant trajectories and place attachments, but also to explore the meaning of this type of epistolary communication in the management and construction of an identity that is scattered around the world but with specific social configurations established between Cape Verdean migrants in Brazil and other places of the world. From this particular case, which is revealing of the originality of the Cape Verde diaspora and culture, we also intend to expand a theoretical and epistemological reflection about the utilization of these types of qualitative methodologies in social sciences.